Perancangan dan Simulasi Energi Meter Digital Satu Phasa Menggunakan Sensor Arus ACS712 - Husnawati; Rossi Passarella; Sutarno; Rendyansyah (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2013)
The energy meter is a measuring instrument for measuring and knowing the power of used electrical energy on the load/electrical equipment connected over given time. Digital energy meter is currently in Indonesia is growing very rapidly, the researchers conducted a study to develop a system that can calculate the power and cost .This paper describes a design and simulation of digital energy meter using current sensor ACS712. The motivation of this study is based on the service charging Hand - Phone (HP) in places such as restaurants. HP charging a fee is charged by the absence of clear standards. With this equipment, the cost of charging can be set based on power consumption, as well as the physical form of portable, in addition to the cost per - KWH can be inserted. In the implementation of this research, several steps must be passed, one of which is the initial stage, which emphasizes the conceptual design of the algorithms and hardware. The results of this initial phase are test simulation algorithm that shows the average value of error is less than 1 % , this means that the algorithm can work well and can be used for the next step ( development).